Variasi Tuturan Basa Walikan dalam Sosial Media: Studi Kasus Komunitas Pemuda-Pemudi di Kota Malang - Rizqy, Muhammad Hifni Sahila; Suryadi, Muhammad (Universitas Pendidikan Indonesia, 2023)
The use of the walikan language as an expression of pride in identity in the Malang youth community has different variations depending on the speakers. The unique variations of the walikan bases can arise due to regional and gender differences between men and women. This study aims to examine how the unique variations of basa walikan can occur based on differences in social strata and gender using a socio-dialectological approach. Through a socio-dialectological approach, it can be known about the variations in the language used by the Malang youth community in using digital tools. This research uses a descriptive-qualitative approach. The data collection technique uses the listening and taking notes technique which in this case is represented through listening activities and being directly involved in communication using the Walikan language through social media applications, namely Instagram. Another technique used to further deepen the analysis is the interview technique. In addition, the equating comparison technique and the differential comparison technique were also used to analyze the data that had been collected. The results of this study indicate that there is a unique variation of the walikan base used by Malang youth, namely, the walikan base variation in the lexicon order, speech acts, and semantics.